The Oxford Handbook of Media Psychology 2013
DOI: 10.1093/oxfordhb/9780195398809.013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Media Practice: How Adolescents Select, Engage with, and Are Affected by Sexual Media

Abstract: This chapter focuses on the role media play in the sexual socialization of adolescents and emerging adults in modern societies. The review of relevant research and theory is organized around the Sexual Media Practice Model’s core components of identity, selection, engagement, and application, which are based on the following assumptions: (1) media consumers are active participants and sometimes content producers; (2) selection and use of sexual media are motivated by the adolescent’s identity or sexual self-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 7 publications
2
61
0
Order By: Relevance
“…According to the Media Practice Model (Steele, 1999;Steele & Brown, 1995), adolescents' selection of sexual media content, their interactions with such content, and the application or reproductions of media in their lives, are the results of continuous interactions between the media, the beliefs that adolescents already have, and their everyday experiences and behavior. Adolescents are thus more likely to use and produce media content that is in line with their everyday experiences and attitudes (Shafer et al, 2013;Steele, 1999), including their gender role orientation. In this context, SNSs are particularly relevant to study as they are platforms in which both the exposure to and the production of sexual content take place.…”
Section: Predicting Adolescents' (Exposure To) Sexy Self-presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Media Practice Model (Steele, 1999;Steele & Brown, 1995), adolescents' selection of sexual media content, their interactions with such content, and the application or reproductions of media in their lives, are the results of continuous interactions between the media, the beliefs that adolescents already have, and their everyday experiences and behavior. Adolescents are thus more likely to use and produce media content that is in line with their everyday experiences and attitudes (Shafer et al, 2013;Steele, 1999), including their gender role orientation. In this context, SNSs are particularly relevant to study as they are platforms in which both the exposure to and the production of sexual content take place.…”
Section: Predicting Adolescents' (Exposure To) Sexy Self-presentationmentioning
confidence: 99%
“…The past years have seen a growing interest in adolescents' behavior on social networking sites (SNSs) (e.g., boyd, 2007;Lenhart, Purcell, Smith, & Zickuhr, 2010;Livingstone, 2008;Livingstone & Brake, 2010;Shafer, Bobkowski, & Brown, 2013). In particular, adolescents' sexual behavior on SNSs, in the form of visual sexy self-presentation, has received increasing attention by scholars (e.g., Crescenzi, Araüna, & Tortajada, 2013;Kapidzic & Herring, 2015;Moreno, Parks, Zimmerman, Brito, & Christakis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sexting could be considered a self‐objectifying behavior for female adolescents whereby seeking approval for sexual appeal is prioritized over preventing negative outcomes (such as mass distribution of a nude photo). Understanding potentially self‐objectifying behaviors as part of the sexual media practice model (Shafer et al., ) is important because self‐objectification has been linked with negative health outcomes such as depression, anxiety, disordered eating, substance use, and less condom use (Carr & Szymanski, ; Grabe & Hyde, ; López‐Guimerà, Levine, Sánchez‐Carracedo, & Fauquet, ). Thus, social media and sexting behaviors may have important implications for female adolescents’ health.…”
Section: Internet Pornography and Sexual Scriptsmentioning
confidence: 99%
“…Consistent with the sexual media practice model (Shafer et al, 2013) and prior research which found online sexual behaviors to cluster into trajectories of low, moderate, and high risk (Baumgartner et al, 2012), it was expected that at least three classes with the following characteristics would emerge: (1) high probabilities of online sexual self-presentation behaviors (e.g., sexualized social media presentation and sexting), (2) high probabilities of seeking Internet pornography and cybersex/role-play experiences, but low probabilities of sexual self-presentation behaviors, and (3) low probabilities of all online sexual experiences. Due to prior findings that maltreated youth as well as youth from less cohesive families engage in more online sexual behaviors (Baumgartner et al, 2012;Noll et al, 2009Noll et al, , 2013, it was also expected that female adolescents who had been maltreated would be less likely to be members of a class with little to no online sexual experiences.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation